Razvojna politika in razvojni klubi v Evropi - Senjur, Marjan (Teorija in praksa, 2007)
The article deals with the question of growth policy. The main idea is that on the basis of economic theory of growth many growth policies are possible. A particular growth policy depends on theory of growth and on social context of a given country. The article attempts to narrow the range of possible growth policies by forming development clubs. A development club is being formed by a group of countries with similar growth characteristics. Three development groups are being identified in Europe. Only one of them could be recognised as a development club. For different development groups different broad growth policies could be formed. The European Union should therefore have two and not just one growth policies for its member countries. A concept of development clubs and groups is applied to analyse the effects of globalization on different groups of European countries.
Keywords: Economy; Gospodarstvo; Economic growth; Ekonomska rast; Development policy; Razvojna politika; Konkurenčnost; Competitiveness; Globalisation; Globalizacija; globalization; Europe; Evropa